Minds, Brains, and Capacities: Situated Cognition and Neo-Aristotelianism - Glock, Hans-Johann (Frontiers in Psychology, 2020)
This article compares situated cognition to contemporary Neo-Aristotelian approaches to the mind. The article distinguishes two components in this paradigm: an Aristotelian essentialism which is alien to situated cognition and a Wittgensteinian 'capacity approach' to the mind which is not just congenial to it but provides important conceptual and argumentative resources in defending social cognition against orthodox cognitive (neuro-)science. It focuses on a central tenet of that orthodoxy. According to what I call 'encephalocentrism', cognition is primarily or even exclusively a computational process occurring inside the brain. Neo-Aristotelians accuse this claim of committing a 'homuncular' (Kenny) or 'mereological fallacy' (Bennett and Hacker). The article explains why the label 'fallacy' is misleading, reconstructs the argument to the effectthat encephalocentric applications of psychological predicates to the brain and its parts amount to a category mistake, and defends this argument against objections by Dennett, Searle and Figdor. At the same time it criticizes the Neo-Aristotelian denial that the brain is the organ of cognition. It ends by suggesting ways in which the capacity approach and situated cognition might be combined to provide a realistic and ecologically sound picture of cognition as a suite of powers that flesh-and-blood animals exercise within their physical and social environments.